Weapons for Witnessing: American Street Preaching and the Rhythms of War - Byron, Kyle (Religion and society, 2020)
Drawing on observations of the performances of street preachers in the United States - as well as the texts that inform them - this article explores the concept of rhythm within and beyond the anthropology of religion. More specifically, it develops an expansive concept of rhythm as multiple and interactive, focusing not on a singular rhythm, but on the rhythmic translations that shape the practice of street preaching. First, I argue that the material rhythms of urban infrastructure constrain the narrative rhythms of the street preacher's sermon, producing a distinct homiletics. I then suggest that the ideological rhythms of war animate the narrative rhythms of the street preacher's sermon, linking military strategies with tactics of evangelism. Examining the material, narrative, and ideological rhythms of streets, sermons, and military doctrine, this article advances an analytic framework whereby the intersecting rhythmic tensions that shape performance can be registered.